2017
DOI: 10.1534/g3.116.037556
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a High-Density American Cranberry (Vaccinium macrocarponAit.) Composite Map Using Genotyping-by-Sequencing for Multi-pedigree Linkage Mapping

Abstract: The American cranberry (Vaccinium macrocarpon Ait.) is a recently domesticated, economically important, fruit crop with limited molecular resources. New genetic resources could accelerate genetic gain in cranberry through characterization of its genomic structure and by enabling molecular-assisted breeding strategies. To increase the availability of cranberry genomic resources, genotyping-by-sequencing (GBS) was used to discover and genotype thousands of single nucleotide polymorphisms (SNPs) within three inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 71 publications
0
42
0
Order By: Relevance
“…The LOD score threshold to call significant QTL was calculated using a permutation test (1000 permutations) and a nominal significance level of 5%. We used a high-density composite map produced with 6073 markers spanning 12 linkage groups and a total length of 1130.42 cM (Schlautman et al 2017); because of the high density of the markers used here, no additional marker imputation was needed. We identified significant peaks automatically using the function big.peaks.col from the package Fragman (Covarrubias-Pazaran et al 2016b); QTLs separated from each other by more than 20 cM were considered different.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOD score threshold to call significant QTL was calculated using a permutation test (1000 permutations) and a nominal significance level of 5%. We used a high-density composite map produced with 6073 markers spanning 12 linkage groups and a total length of 1130.42 cM (Schlautman et al 2017); because of the high density of the markers used here, no additional marker imputation was needed. We identified significant peaks automatically using the function big.peaks.col from the package Fragman (Covarrubias-Pazaran et al 2016b); QTLs separated from each other by more than 20 cM were considered different.…”
Section: Methodsmentioning
confidence: 99%
“…Georgi et al (2013) published the first SSRbased genetic map of American cranberry, and reported several QTLs for yield, fruit weight, titratable acidity and proanthocyanidin content. With the recent development of high-density genetic maps (Schlautman et al 2015, 2017; Covarrubias-Pazaran et al 2016a; Daverdin et al 2017), the creation of new mapping populations (Schlautman et al 2015), the development of modern massive phenotyping techniques (Houle et al 2010), and the availability of the cranberry genome (Polashock et al 2014), the identification and fine-mapping of loci governing major phytochemicals in cranberry fruit are crucial for the future breeding of cultivars with enhanced phytochemical properties for processing and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…A high-density linkage map has only been built for cranberry ( Vaccinium macrocarpon Ait.) (Schlautman et al, 2017), a diploid-relative of blueberry.…”
Section: Introductionmentioning
confidence: 99%
“…Georgi and collaborators (2013) published the first SSR-based genetic map and reported several quantitative trait loci (QTL) for yield related traits and important phytochemicals. Subsequently, high-density genetic maps as well as more multi-trait QTL studies became available [22][23][24][25][26][27]. In addition, nuclear [28], plastid [29], and mitochondrial [30] genomes have been published recently.…”
mentioning
confidence: 99%